Site-Specific Immunosuppression in Vascularized Composite Allotransplantation: Prospects and Potential - Jonas T. Schnider; Matthias Weinstock; Jan A. Plock; Mario G. Solari; Raman Venkataramanan; Xin Xiao Zheng; Vijay S. Gorantla (Clinical and Developmental Immunology)
Skin is the most immunogenic component of a vascularized composite allograft (VCA) and is the primary trigger and target of rejection. The skin is directly accessible for visual monitoring of acute rejection (AR) and for directed biopsy, timely therapeutic intervention, and management of AR. Logically, antirejection drugs, biologics, or other agents delivered locally to the VCA may reduce the need for systemic immunosuppression with its adverse effects. Topical FK 506 (tacrolimus) and steroids have been used in clinical VCA as an adjunct to systemic therapy with unclear beneficial effects. However, there are no commercially available topical formulations for other widely used systemic immunosuppressive drugs such as mycophenolic acid, sirolimus, and everolimus. Investigating the site-specific therapeutic effects and efficacy of systemically active agents may enable optimizing the dosing, frequency, and duration of overall immunosuppression in VCA with minimization or elimination of long-term drug-related toxicity.